The Effect of Internal Marketing on the Prosperity of Maqashid Syariah Perspective Employees on Banking in Surakarta - Hamidah, Raisa Aribatul; Tsani, Atika Fikri (Journal of Islamic Economic Laws, 2020)
This study aims to determine the effect of internal marketing consisting of the dimensions of the Company Mission and Development of Human Resources on the welfare of employees from the perspective of Maqashid Syariah on banking in the city of Surakarta. This study uses a questionnaire in primary data collection and a quantitative approach with Multiple Linear Regression analysis. The research sample was 96 employees who worked a minimum of three months in banking in the city of Surakarta. Sampling using accidental sampling technique, namely determination of the sample by chance. Validity and reliability testing is carried out with the help of the SPPS 15 (Statistical Product and Service Solution) program. The result is that Internal Marketing in the Corporate Mission dimension (X1) does not have a significant effect, and the SDI Development (X2) dimension has a significant positive effect of 0.877 on Employee Welfare from the Maqashid Syariah perspective on Banking in Surakarta.